Protection of Consumer Rights in Review from Law Number 8 Of 1999 In E-Commerce Transactions - Wulandari, Wulandari (JLASA (Journal of Law and State Administration), 2023)
Development technology bring impact on the field business trading in a manner online (e-commerce) now growing very rapidly and has swipe system trading conventional going to digital trade. Due to developments e-commerce this needed exists protection right consumer in transaction ecommerce, in law positive in Indonesia protection law for consumer in transaction e-commerce loaded inside regulation Constitution Number 8 of 1998 concerning Protection consumer. Completion Dispute Protection Consumer Completion Dispute in Court Dispute consumer settled in court refers to the conditions Justice general. Constitution Number 8 of 1999 concerning Protection The consumer (UU PK) regulates about election settlement dispute well outside as well as in court depends agreement of the parties to the settlement process dispute protection consumer in court could form lawsuit individual normal lawsuit simple, lawsuit group or lawsuit filed by the agency self-subsistent public protection consumers and government/agencies related. Completion Outside Dispute Court Law no. 8 of 1999 provides authority to the Settlement Body Dispute Consumer for complete dispute outside consumers court. Completion dispute consumer through BPSK is done with method mediation, arbitration, or conciliation